Pengaruh Penggunaan Sistem Pengukuran Kinerja Terhadap Kinerja Manajer Pada Restoran Yang Memakai Jasa GrabFood di Kota Bukittinggi Tahun 2023 - Dhea Sri Amanda; Syuryatman Desri; Muhammad Alung; Abdul Hafid (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study examines the effects of the work measurement system's adoption on the productivity of GrabFood system-using businesses using quantitative methodologies and multiple regression analysis. Primary data from surveys given to Bukittinggi residents were used in this investigation. GrabFood usage by restaurants served as the dependent variable in this study, with the use of performance monitoring systems (X1) and manager performance (X2) acting as independent variables. The use of the performance measuring system (X1) and management performance (X2) has a positive influence on the use of GrabFood services (Y), according to the results of the multiple linear regression test. In light of the overall determination coefficient test findings, the coefficient value of 0.376 (37.6%) which means that the use of the performance measurement system (X1) and manager performance (X2) has an influence of (37.6%) on the use of GrabFood Services (Y). Then Ha Accepted: the use of performance measurement system (X1) and performance manager (X2) has a significant effect together on the use of GrabFood services (Y). while the remaining 0.624 (62.4%) was influenced by other variables